FEASIBILITY OF SHALLOW GROUNDWATER QUALITY AS DRINKING WATER IN BANTAN SARI VILLAGE, BENGKALIS ISLAND, RIAU PROVINCE - Mairizki, Fitri; Putra, Arief Yandra; Dewandra Bagus Eka Putra; Marsela, Belila; Sartika, Reni (JURNAL KATALISATOR, 2024)
Clean water plays a central role in human survival. The majority of clean water comes from groundwater. Shallow groundwater from dug wells does not necessarily have suitable quality for use because it is vulnerable to contamination. Bantan Sari is one of the villages located on Bengkalis Island. Besides having problem related to water availability, this area also has poor shallow groundwater quality. This study aims were to determine the quality of shallow groundwater in the study area and map its feasibility as a source of drinking water. This research is expected to be the basis for further research to improve groundwater quality on Bengkalis Island. The research methods included field data collection and laboratory analysis. The parameters measured consisted of color, TDS, DHL, pH, Fe and Mn levels. Based on the results of study, 14 dug wells were obtained. Groundwater color in study area were colorless (36%), yellow (7%), brown (21%), and reddish brown (36%). Groundwater TDS ranged from 59 mg/l – 560 mg/l. Groundwater DHL ranged from 107 mg/l – 1080 mg/l. Groundwater pH ranged from 6,49 – 6,74. Groundwater Fe levels ranged from 0,3 mg/l – 5,43 mg/l and groundwater Mn levels < 0,4 mg/l. Based on Minister of Health Regulation No.492/Menkes/Per/IV/2010 about drinking water quality requirements, it is known that only 1 sample (7%) is included in the drinkable category while the other 13 samples (93%) are included in non-drinkable category.